Design of Personalized Online Education System of Forestry Science Based on Big Data Technology - Ling Zhang (Forest Chemicals Review)
With the advent of the information age, the cycle of knowledge updating of forestry science is becoming shorter and shorter. How to make teaching and training of forestry science meet the needs of people in different places and learning time, the traditional face-to-face education of forestry science has been inadequate in this regard. In this case, modern distance education came into being. Its advantage is that students can interact with teachers and complete learning tasks when time and space are not unified. With the combination of computer aided instruction (CAI) and Internet technology, online education based on Web has become a new trend in the development of modern education. This paper takes the distance education system as an example. In the work practice, according to the performance improvement needs of distance education system. This paper uses web testing technology to obtain the mainstream network equipment, network transmission bandwidth, system response, network load and other information to comprehensively analyze and record the use of the system. In this paper, through the analysis of the network test report, according to the report to develop the best network optimization strategy. After the network is optimized, it is tested and optimized again to improve the network performance. So as to provide a comprehensive, convenient, intuitive and accurate test and optimization scheme for distance education network. The system can reduce the heavy performance guarantee work caused by the continuous complexity of online education network application, and provide convenience for online education application system.